Case report: Chronological symptom profile after cessation of overdose zolpidem in a patient with comorbid bipolar disorder—from anxiety, craving, paresthesia and influenza-like symptoms to seizures and hallucinations - Mao, Zi-xin; Yang, Xia; Wang, Hui-yao; Guo, Wan-jun (Frontiers in Psychiatry, 2022)
Introduction: Insomnia is a major public health problem that determines quality of life. Among the many causes of insomnia, psychological factors have an important influence on the process, duration of insomnia, help-seeking behavior and treatment choice. Regarding medical treatment, zolpidem is always chosen to treat acute and transient insomnia due to its few side effects. Although some randomized controlled trials have verified its safety, zolpidem abuse and withdrawal reactions have been reported in recent years. Case Report: A 25-year-old unmarried man with a college degree who worked as a graphic designer was referred and admitted to the inpatient ward for a chief complaint of “alternative episodes of lowering and elevation of mood for 10 years, overdosage use of zolpidem for two years”. He underwent a time-dependent withdrawal reaction after admission. It was characterized by rebound insomnia, anxiety, craving, skin paresthesia, influenza-like symptoms, tonic‒clonic-type seizures and hallucinations. At the one-year follow-up, he did not exhibit any remaining withdrawal symptoms. Discussion: The acute cessation of overdosage zolpidem use causes a series of withdrawal symptoms that manifest in chronological order. Additionally, long-term benzodiazepine exposure has potential influences on zolpidem dependence/tolerance. However, patients with a history of abuse or dependence or mental disorders seem to be at risk of drug abuse. Clinicians should be alert to the potential for zolpidem dependence and addiction. Once the acute cessation of overdosage zolpidem use occurs, the potential of the withdrawal reaction needs to be considered and addressed properly.